Two-dimensional CdS intercalated ZnO nanorods: a concise study on interfacial band structure modification. Issue 57 (31st May 2016) - Oleiwi, Hind Fadhil; Tan, Sin Tee; Lee, Hock Beng; Yap, Chi Chin; Ginting, Riski Titian; Zakaria, Azmi; Alshanableh, Abdelelah; Tan, Chun Hui; Haji Jumali, Mohammad Hafizuddin; Yahaya, Muhammad; Talib, Zainal Abidin
Abstract : The intercalation of CdS on ZnO nanorods modified the optical band gap effectively and improved the solar cell performance significantly. Abstract : The controllable growth of metal sulfide–metal oxide based nanomaterials with a tunable band gap structure is vital in the fabrication of new generation optoelectronic devices. In this paper, two-dimensional hierarchical CdS/ZnO nanorod arrays were successfully grown via a low temperature hydrothermal-SILAR method. A concise mechanism related to the surface and band gap modification on the CdS/ZnO nanorods was investigated under various CdS deposition cycles ( N ). The diameter and surface roughness properties of the sample were found to be linearly dependent on the value of N . A bathochromic shift in the optical energy band gap revealed the quantum size effects of the CdS/ZnO nanorods, as well as the induced interface band state and energy band split in the ZnO band state. An impressive improvement in the crystallinity of the sample was also observed under the CdS treatment. The correlation between the optical band gap and photovoltaic efficiency was evaluated. The results proved that the ZnO nanorod/CdS devices exhibited a threefold higher power conversion efficiency in comparison to a pristine ZnO nanorod device.